Assessment of Anthropometric Indicators of Employees As a Tool for Developing Corporate Health Programs - A. I. Vvedensky; Yu. G. Egiazarov (Здоровье мегаполиса, 2025)
Background. Modern working conditions place high demands on the physical and mental health of employees. The increasing trend towards office-based work, characterized by low physical activity and poor nutrition, leads to an increase in the number of occupational diseases, decreased working capacity, and a deterioration in the quality of life of employees. Consequently, corporate health programs are becoming an important tool for improving not only the physical health of employees but also their motivation, job satisfaction, and productivity. Anthropometric indices of employees are important indicators of a person's physical condition, and they also help to identify issues related to obesity, physical inactivity, metabolic disorders, and other conditions.The purpose of the study was to identify the role of anthropometric indices in the development and implementation of corporate health programs aimed at improving the physical health and productivity of employees.Materials and methods. The study used an integrated approach, including a theoretical analysis of scientific literature, collection and generalization of statistical data, and examination of practical experience in implementing corporate health programs. The main focus was on the study of anthropometric indices such as body mass index, waist and hip circumference, and their impact on employee health and the development of personalized health programs.Results. The development of corporate health programs based on anthropometric data is an innovative approach to personnel management. Taking into account the anthropometric parameters of employees allows you to create personalized and effective prevention and wellness strategies that not only contribute to improving employee health but also provide long-term economic benefits for companies.